Peptide-Based Drug Design - Otvos, Laszlo; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2008)
Due to their high specificity and low toxicity profile, peptides have once again become central to the development of new drugs. In Peptide-Based Drug Design: Methods and Protocols, expert researchers provide a handbook which offers a selection of research and production tools suitable for transforming a promising protein fragment or stand-alone native peptide into a pharmaceutically acceptable composition. The volume delves into contemporary, cutting-edge subjects such as hit isolation and target validation, computer-aided design, sequence modifications to satisfy pharmacologists, in vivo stability and imaging, and the actual production of difficult sequences. Written in the highly successful Methods in Molecular Biology™ series format, chapters include readily reproducible, step-by-step laboratory protocols, lists of materials, and the Notes section, which highlights tips on troubleshooting and avoiding known pitfalls. Comprehensive and up-to-date, Peptide-Based Drug Design: Methods and Protocols shows its subject to be an independent science on the rise, and provides scientists with a clear, concise guide for continuing this vital research.
Peptide-Based Drug Design: Here and Now -- Strategies for the Discovery, Isolation, and Characterization of Natural Bioactive Peptides from the Immune System of Invertebrates -- Sequence Analysis of Antimicrobial Peptides by Tandem Mass Spectrometry -- The Spot Technique: Synthesis and Screening of Peptide Macroarrays on Cellulose Membranes -- Analysis of A? Interactions Using ProteinChip Technology -- NMR in Peptide Drug Development -- Molecular Dynamics Simulations of Peptides -- Short Linear Cationic Antimicrobial Peptides: Screening, Optimizing, and Prediction -- Investigating the Mode of Action of Proline-Rich Antimicrobial Peptides Using a Genetic Approach: A Tool to Identify New Bacterial Targets Amenable to the Design of Novel Antibiotics -- Serum Stability of Peptides -- Preparation of Glycosylated Amino Acids Suitable for Fmoc Solid-Phase Assembly -- Synthesis of O-Phosphopeptides on Solid Phase -- Peptidomimetics: Fmoc Solid-Phase Pseudopeptide Synthesis -- Synthesis of Toll-Like Receptor-2 Targeting Lipopeptides as Self-Adjuvanting Vaccines -- Synthesis of a Multivalent, Multiepitope Vaccine Construct -- Cysteine-Containing Fusion Tag for Site-Specific Conjugation of Therapeutic and Imaging Agents to Targeting Proteins.
Keywords: Pharmacology; Medicinal chemistry; Pharmacology/Toxicology.; Medicinal Chemistry